Twists and turns: spontaneous torsion of accessory liver lobe and gallbladder—diagnostic challenges and surgical interventions—a case report - Charaa, Soumaya; Frandon, Julien; Touimi Benjelloun, Ghizlane; Tessier, Benoit (Frontiers in Pediatrics, 2025)
An accessory liver lobe (ALL) represents a rare congenital variation of liver tissue, typically resulting from focal excessive development of liver tissue. Torsion of such lobes, though rare, can precipitate a severe surgical crisis due to hepatic ischemia and failure. We report a case involving a 9-year-old patient who was admitted with acute epigastric pain. Doppler ultrasound and contrast-enhanced CT scans revealed a heterogeneous, avascular mass with displacement of the gallbladder, which had a thickened wall. During laparotomy, a twisted, congested ALL along with the gallbladder was surgically removed. Diagnostic imaging, particularly computed tomography (CT), plays a crucial role in the rapid identification of causes behind acute abdominal pain, necessitating meticulous analysis of CT scans. We share the findings from imaging and surgery to enhance awareness of this rare condition.